Osteochondral autograft transfer for the treatment of osteochondritis dissecans of the medial femoral condyle in dogs - Fitzpatrick, N.; Yeadon, R.; van Terheijden, C.; Smith, T. J. (Veterinary and Comparative Orthopaedics and Traumatology, 2012)
Objective: To describe the clinical application of osteochondral autograft transfer procedure for the treatment of osteochondritis dissecans (OCD) of the canine medial femoral condyle and to report clinical and force plate outcomes.Methods: Osteochondral autograft transfer (OATS™; Arthrex, Naples FL, USA) instrumentation was employed in six stifle joints of five dogs. Clinical examination was performed preoperatively and at two to three weeks, six to eight weeks, 12–18 weeks and at >22 months postoperatively. Radiography and arthroscopy were performed preoperatively and 12–18 weeks postoperatively. The followup examinations performed at 22 to 56 months included radiography, questionnaire completion with the owner, and force plate gait evaluation.Results: Articular surface reconstruction was radiographically (for 6 stifle joints) and arthroscopically (for 5 stifle joints) maintained at 12–18 weeks. Subjectively-assessed lameness resolved in five out of six stifles by the 12 to 18 week reassessment. Morbidity included lateral patellar luxation at seven weeks and cranial cruciate ligament rupture at 11 months postoperatively. At the >22 month re-evaluation examination, subjectively-assessed lameness and signs of discomfort were minimal. Owner perceptions of outcome were positive; force plate assessment of gait indicated that weight bearing on three out of six OAT implanted limbs was less than the contralateral limb, but these comparisons were not evaluated statistically. A progression in the development of osteophytes was radiographically evident.Clinical significance: The OAT procedure can reconstruct medial femoral condyle OCD defects in dogs. Long-term lameness and progressive osteophytosis may occur but can be associated with other pathology such as cruciate ligament insufficiency.
Keywords: Osteochondral; autograft; osteochondritis dissecans; stifle; canine